The Prevalence of Hearing Impairment by Age and Gender in a Population-based Study - Alimohamad ASGHARI; Mohammad FARHADI; Ahmad DANESHI; Mehdi KHABAZKHOOB; Saman MOHAZZAB-TORABI; Maryam JALESSI; Hesamedin EMAMJOMEH (Tehran University of Medical Sciences, 2017)
Background: This study aimed to determine the prevalence of hearing impairment (HI) by age and gender in a population aged 5 yr and older residing in Tehran, Iran. Methods: In this cross-sectional study, 140 clusters each including 10 households from Tehran, Iran were sampled between 2012 and 2013 using cluster random sampling. Trained audiologists examined the participants during face-to-face interviews. The hearing of the participants was evaluated before the removal of wax or other foreign bodies. In this study, HI was categorized as mild (grade 1, 26-40 db), moderate (grade 2, 41-60 db), severe (grade 3, 61-80 db), and deaf (grade 5, 81 db or more). All participants signed informed consent forms. The SATA software was used for data analysis. Results: Of 6521 individuals, 4370 (67%) were interviewed. The prevalence of HI (auditory threshold of 0.5, 1, 2, 4 KHz and more than 25 db in the better ear) was 14.27 (11.53-17.91) of whom 9.52 (7.07-11.98) had grade 1, 4.04 (3.02-5.06) had grade 2, 0.67 (0.33-1.02) had grade 3 HI and 0.48 (0.16-0.8) were deaf. About 5.19% of the participants had disabling hearing impairment. All HI grades increased significantly with age but no significant difference was observed between men and women. Conclusion: The considerable prevalence of HI in Iran in comparison with other developing countries, with regards to the trend of aging in the population, seems concerning. The results of the study could be used as a treatment and research guideline for future works in the area of policymaking and plan to decrease these disorders.